2015
DOI: 10.1016/j.jcrs.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset methicillin-resistant Staphylococcus aureus keratitis and late-onset infectious keratitis in astigmatic keratotomy incision following femtosecond laser–assisted cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Earlier in 2015, Chou et al from USA had reported a case of femtolaser LRI which showed infiltration due to methicillin-resistant Staphylococcus aureus after an uneventful FLACS. [2] Recently, in 2018, Grillo et al reported a case of late onset Microsporidial keratitis following an uneventful FLACS with femtosecond laser AK in the USA. [3] In India, Haripriya et al had reported a case of keratitis and a case of endophthalmitis following manual LRI in phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier in 2015, Chou et al from USA had reported a case of femtolaser LRI which showed infiltration due to methicillin-resistant Staphylococcus aureus after an uneventful FLACS. [2] Recently, in 2018, Grillo et al reported a case of late onset Microsporidial keratitis following an uneventful FLACS with femtosecond laser AK in the USA. [3] In India, Haripriya et al had reported a case of keratitis and a case of endophthalmitis following manual LRI in phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…Arcuate keratotomy (AK) is an efficacious intraoperative procedure for reduction of pre-existing corneal astigmatism between 0.5 and 3.0 D.[1] However, it may also act as an additional route of entry of micro-organisms, increasing the risk of post-operative infection. [234] The advent of femtosecond laser has made it possible to create highly accurate and well-structured AKs. We report first case of femtosecond laser AK infiltration from south-east Asia, and also propose recommendations for prevention and treatment of these cases.…”
mentioning
confidence: 99%
“…In FS-AK, the cornea wounds are closed, which can decrease the incidence of infection. However, any corneal incisions have the risk of complications including infection, inflammation, wound gaping, scarring, and unintended full thickness incisions [ 51 , 63 , 64 ]. In general, infection after FS-AK alone or FS-AK performed in combination with cataract surgery is rare.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In general, infection after FS-AK alone or FS-AK performed in combination with cataract surgery is rare. A few cases of keratitis after FS-AK were reported [ 63 , 65 , 66 ]. Thus, FS-AK is generally considered to be safe.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Infection after femtosecond laser-assisted astigmatic keratotomy Infection, although rare, has been reported after FSAK [30]. One patient developed a methicillin-resistant Staphlococcus aureus (MRSA) corneal infiltrate in one of two paired astigmatic keratotomy incisions 3 weeks after having femtosecond-enabled cataract surgery.…”
Section: Reported Complications Of Femtosecond Astigmatic Keratotomymentioning
confidence: 99%